Ecology and fisheries of mud crab scylla serrata in Lawele Bay, Southeast Sulawesi, Indonesia. - La Sara (Miagao, Iloilo College of Fisheries, University of the Philippines Visayas, 2001)
Based on similarity of natural features of the stations studied, there were three habitats of S. serrate in Lawele Bay. Habitat A was characterized by shallow water depth, low salinity, high turbidity, muddy substrate, the widest intertidal flat and the thickest mangrove vegetation This habitat was preferred by S. serrate since they were frequently caught there. The characteristics of habitat B were moderate water depth, salinity and turbidity, clay loam substrate, narrow intertidal flat and mangrove vegetation. This habitat was less preferred by S. serrate since only 11.87% caught. The characteristics of habitat C were different with that of habitat A and B. This habitat was not preferred by S. serrate because only 1.19% caught.Size distribution of S. serrate was affected by tidal cycles and habitants. During flood tide, frequency of male juveniles, subadults and adults of both sexes was higher than ebb tide. Most of these were frequently caught at habitat A. The relative abundant between sexes was significantly different, while among habitats was also significantly different except between habitats B and C. S. serrate in Lawele Bay may be found all year round with two peaks of abundance. A major peak was in July and a minor peak in February. The lowest relative abundance was in December. However, seasonal relative depended on sexes and tidal cycles. During flood tide, temperature, turbidity and TSS were significantly correlated with males, while salinity, turbidity and TSS appeared to be significantly correlated with females. During ebb tide, water depth, current velocity and pH had significant correlation only with males, while no water parameter had significant correlation with females.
Dissertation (Doctor of Philosophy in Fisheries - Aquaculture) - University of the Philippines Visayas, December 2001.
Keywords: Mud Crab; Ecology; Fisheries